Analysis of the Role of STEAM Education in Improving Critical Thinking Skills for Sustainable Development - Krisna Muftidafila Ilham Rosyida; Binar Kurnia Prahani; Muhammed Akif Kurtuluş (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2025)
Objective: The era of Society 5.0 requires individuals to have strong critical thinking skills. STEAM learning improves critical thinking skills by integrating science, technology, engineering, art, and math. This study aims to systematically review the existing literature on the effectiveness of STEAM learning in improving students' critical thinking skills, especially in achieving SDG point 4, namely quality education. Method: This research uses the literature review method. A total of 20 relevant articles that met the inclusion criteria were selected and analyzed in depth to identify key findings related to the impact of STEAM learning on the development of critical thinking skills. Results: The analysis shows that STEAM learning has significant potential in improving students' critical thinking skills. Some key findings include the following: STEAM learning stimulates students to think critically, creatively, and analytically in solving problems; STEAM facilitates the development of collaboration, communication, and problem-solving skills that are relevant to the demands of the future world of work, and STEAM learning contributes to the achievement of SDGs point 4 by providing quality and appropriate education for students. Novelty: This research contributes to the field of education by presenting a comprehensive review of the effectiveness of STEAM learning in improving critical thinking skills in the context of achieving SDGs point 4. The results of this research can be a reference for educators, curriculum developers, and policymakers in designing effective learning programs to prepare young people for future challenges.